(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The aim of this study is to study the Physical and chemical properties, classification, toxicity and hazards of Pesticide. In this study we focus the Physical and chemical properties and stages of intoxication, use of pesticide and history of pesticides. Also we this study the kinds toxicity and hazards of pesticides. Classification by type of exposure and body system affected is also the part of study.